Penyuluhan Cara Penyimpanan Asi Pada Ibu Bekerja Dengan Peningkatan Pengetahuan Cara Penyimpanan ASI - Martina Fitriyaningrum; Winarsih; Sri Martuti (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2018)
Background: The provision of breastfeeding in Indonesia has not been fully implemented. Efforts toimprove behavior feeding is weak. The main problems are socio-cultural factors, awareness of theimportance of breast milk, health services, incessant promotion of formula milk and working mothers. Thecoverage of breastfeeding in the Demangrejo village area of 13 infants aged 0-6 months who were stillexclusively breastfed was 4 babies (30.80%) and those who were not exclusively breastfed were 9 babies(69.24%).Purpose: To evaluate the effectiveness of counseling about how to strorage breastmilk with improving ofknowledge breastmilk storage methods for working mother in posyandu Demangrejo Kulon Progo 2016.Methods: quasi experiment with one group pretest-posttest design research design. Research time is AprilMay 2016. The research location is in Posyandu, Demangrejo Village, Kulon Progo Yogyakarta. The sampleused was nursing mothers who worked. This research analyzes the data used is Wilcoxon testResults: The results of the study, based on analysis of the wilcoxon data pretest and posttest obtainedvalue Z count -4,419 and P-value is 0.000 (p<0,05), it means there was a relations counseling storagemethods breastmilk on the work with increased knwoledge storage methods breastmilk in posyanduDemangrejo Kulon Progo.Conclusions: There is relations counseling storage methods breastmilk on the work with increasedknwoledge storage methods breastmilk in posyandu Demangrejo Kulon Progo.Keyword : Counseling, Enhancement, BreastmilkIN